A Comparative Study of the Attitudes of Muslim and Non-Muslim Prospective Teachers towards Teaching Professionâ - Parvez, Mohammad; Shakir, Mohd (EDUCARE, 2014)
ABSTRACT: Securing the right type of prospective teachers for training is very crucial. Unless such prospective teachers are found our secondary schools cannot deliver as per our expectations. Therefore, for the professional preparation of prospective teachers, the study of attitudes held by them is very important. This study was conducted to study the attitudes of Muslim and Non-Muslim prospective teachers towards teaching profession. A sample of 360 prospective teachers i.e. 200 Muslim and 160 Non-Muslim prospective teachers was taken through purposive sampling technique. Teacher Attitude Inventory (TAI) developed by S.P. Ahluwalia (2007) was used to collect the data. Mean, SD (Standard Deviation), and t-test were used for the analysis of the data. Research findings revealed not significant differences in the attitudes of Muslim and Non-Muslim prospective teachers; Muslim and Non-Muslim male prospective teachers; Muslim and Non-Muslim female prospective teachers; Muslim and Non-Muslim Science prospective teachers; Muslim and Non-Muslim Social Science prospective teachers; Muslim and Non-Muslim prospective teachers studying in public B.Ed. (Bachelor of Education) institutions; whereas a significant difference was found between the attitudes of Muslim and Non-Muslim prospective teachers studying in private B.Ed. institutions towards teaching profession. Muslim prospective teachers studying in private B.Ed. institutions had a more favourable attitude towards teaching profession as compared to Non-Muslim prospective teachers studying in private B.Ed. institutions.KEY WORDS: Prospective teachers, Muslim and Non-Muslim teachers, teaching profession, favourable and unfavourable attitudes, and public and private B.Ed. institutions.Â Â About the Authors: Dr. Mohammad Parvez is an Associate Professor at the Department of Education AMU (Aligarh Muslim University), Aligarh, 202002 Uttar Pradesh, India; and Dr. Mohd Shakir is an Assistant Professor at the Department of Education AMU, Murshidabad Centre, 742223 West Bengal, India. For academic purposes, the authors can be contacted via e-mails at: mparvez9@yahoo.co.in and Â aligarhshakir@gmail.comHow to cite this article? Parvez, Mohammad & Mohd Shakir. (2014). âA Comparative Study of the Attitudes of Muslim and Non-Muslim Prospective Teachers towards Teaching Professionâ in EDUCARE: International Journal for Educational Studies, Vol.7(1) August, pp.67-74. Bandung, Indonesia: Minda Masagi Press and UMP Purwokerto, ISSN 1979-7877. Chronicle of the article: Accepted (April 15, 2014); Revised (June 1, 2014); and Published (August 17, 2014).